2022
DOI: 10.7717/peerj.12695
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the composition and predicted functions of the intestinal microbiome of obese and normal weight adult dogs

Abstract: Obesity is a multifactorial nutritional disorder highly prevalent in dogs, observed in developed and developing countries. It is estimated that over 40% of the canine population suffers from obesity, which manifests in an increased risk of chronic osteoarticular, metabolic, and cardiovascular diseases. The intestinal microbiome of obese animals shows increases in the abundance of certain members capable of extracting energy from complex polysaccharides. The objective of this study was to compare the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 89 publications
1
8
0
3
Order By: Relevance
“…In addition, several studies have reported that the relative abundance of Bifidobacterium is lower in mice fed a high-fat diet 83 , 84 . In this study, Bifidobacterium exhibited a strong negative correlation with Peptoclostridium and Blautia , which have previously been associated with obesity in dogs 20 , 85 , and a strong positive correlation with Lactobacillus , Sellimonas , and Negativibacillus . A previous study suggested that Lactobacillus may serve as a potential probiotic for dogs 27 and Sellimonas plays an important role in gut recovery homeostasis 86 .…”
Section: Discussionsupporting
confidence: 69%
“…In addition, several studies have reported that the relative abundance of Bifidobacterium is lower in mice fed a high-fat diet 83 , 84 . In this study, Bifidobacterium exhibited a strong negative correlation with Peptoclostridium and Blautia , which have previously been associated with obesity in dogs 20 , 85 , and a strong positive correlation with Lactobacillus , Sellimonas , and Negativibacillus . A previous study suggested that Lactobacillus may serve as a potential probiotic for dogs 27 and Sellimonas plays an important role in gut recovery homeostasis 86 .…”
Section: Discussionsupporting
confidence: 69%
“…We compared our results and data with those of other studies 43,50,51,52,53,54 ( Supplementary Data 6 , Supplementary Fig. 7 ), all of which focus on a single aspect of the canine gut microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…Estima-se que a obesidade seja um distúrbio que acomete mais de 40% da população canina mundial (Thomson et al, 2022) e, mediante tais dados, a intervenção do médico veterinário para o diagnóstico e o tratamento do animal obeso é de suma importância. Segundo German et al (2018), médicos-veterinários ainda não consideram a problemática obesidade e sobrepeso com a seriedade necessária, uma vez que os profissionais dificilmente registram o peso e a condição corporal durante as consultas veterinárias.…”
Section: Casuísticaunclassified
“…A obesidade e o sobrepeso animal são de origem multifatorial e não se tratam apenas da adiposidade, ou seja, do acúmulo excessivo de tecido adiposo, mas estão associadas a importantes alterações metabólicas, hormonais, articulares e imunológicas (Andrade Junior, 2019). A obesidade é um dos maiores desafios na saúde do século XXI, estando correlacionada à redução da qualidade de vida, bem como a distúrbios fisiológicos em seres humanos e cães (Muñoz-Prieto et al, 2018;Thomson et al, 2022). Para Aptekmann et al (2014), a manutenção do peso corporal ideal é fator determinante para manutenção da saúde, bem-estar e qualidade de vida.…”
Section: Introductionunclassified